OPTIMIZATION OF PRIMARY COLLECTOR USAGE IN FLOTATION PROCESS AT CONCENTRATOR NO. 3 PT XYZ - ZULFAKAR (NIM: 29107112), DONNY
Economic global crisis began to have impact on business all over the world at the end 2008. Metal price falls significantly. This condition has forced mining company, including PT SRT, to start optimizing production costs and ensuring production yields in as effective as it can. Primary collector is one of the reagents used in flotation process and consumes the highest cost in chemical consumables, more than 30% of total chemical costs. Consumption level of primary collector is driven by dosage implemented in the field. Standard dosage is determined by involving two aspects: selection and implementation. Selection phase is a sequence of processes to find optimum dosage range of primary collector. This study begins with a literature study, then follows by historical data analysis using response surface methodology to produce a recovery model. The model is a function of some variables. After optimum range is confirmed by the model, optimization is continued with the implementation phase including field validation. Control strategy and material availability also play important roles since they ensure set point dosage to be implemented as required, no other constraint. In the production rate as big as PT SRT, the loss of 1% of copper recovery is equivalent with millions of dollar. For that reason every plant changes, including optimization need to carefully examine before initiation. Optimization involves combination of literature study, laboratory test, and historical data analysis. Plant implementation is a second validation and fine tuning method. Tuning is required to conduct because concerns about scale up factor of laboratory test and model error. The objective of this research is to find optimum dosage of primary collector. The dosage is function of feed grade. If the feed grade of 0.7% Cu then required primary collector is 29.8 g/t or 4.3 g/kg Cu. However, if the feed grade increases to 1% Cu it implies on the increase of dosage up to 36.8 g/t or equivalent with 3.7 g/kg Cu. Implementation plan consists of 3 phases, they are: validation, verification, and control. The objective of implementation is to ensure the improvement is real, significant, and permanent